Admissibility test for the EIAS: state of the art of projects’ non-admissibility - Linazasoro, Izaskun; Pelayo Díaz, Constanza (Revista de Derecho Ambiental, 2019)
This article reviews the anticipatory control mechanisms of the environ-mental impact assessment established in our legal system, especially analyzing the admissi-bility test of the projects submitted to the Environmental Impact Assessment System (EIAS). After an identification of the latest projects entered into the EIAS for a year and a half, and those not admitted in the same period, certain differences in criteria and causes for non-admission are identified among the environmental authorities of the different regions of the country when making this determination, which we analyze in great detail, with the aim of proposing certain considerations in the framework of the imminent modification to the SEIA, which are especially related to the need for coordination and coherence of the system, whose absence marks the development of this work. In summary, this paper at-tempts to emphasize the urgent need to systematically, permanently and flexibly regulate the environmental assessment procedure, from the earliest stages of the projects.